Reading the book of Lamentations as a whole : canonical-literary approach to the scripture as divine communicative action - Venter, P.M. (Pieter Michiel), 1947- (University of Pretoria, 2013)
Dissertation (MA(Theology))--University of Pretoria, 2009.